Balancing act : motherhood, marriage, and employment among American women - Spain, Daphne; Bianchi, Suzanne M. (Russell Sage Foundation, 1996)
Balancing Act draws upon multiple census and survey sources to detail the shifting conditions under which women balance their roles as mothers, wives, and breadwinners. The authors show how women have made great strides in education, where female college enrollment now exceeds that of males, and in the workplace, where women now enter a wider variety of occupations and stay on the job longer than previous generations, even after becoming wives and mothers. Despite these gains, however, many American women are struggling to make ends meet. Lower-paying service positions remain predominantly female and, although the salary gap between men and women has shrunk, women are still paid less for similar work. Also, as women continue to establish a greater presence outside the home, many have delayed marriage and motherhood. Marked jumps in divorce and out-of-wedlock childbirth have given rise to increasing numbers of female-headed households. Balancing Act focuses on how American women juggle the simultaneous demands of caregiving and wage earning and compares the patterns of their lives with those of women in other countries. The United States is the only industrialized nation without policies to support working mothers; most telling is the absence of subsidized child-care services. As a consequence, the risk of poverty is the single greatest danger facing American mothers, with African American women the most adversely affected.